STUDI PREVALENSI MASALAH GIZI GANDA ANAK SEKOLAH DASAR DAN MADRASAH IBTIDAIYAH DI KOTA LUBUKLINGGAU - Nuryanto Nuryanto; Podojoyo Podojoyo; Yulianto Yulianto (Publikasi Penelitian Terapan dan Kebijakan, 2020)
Nutritional status represent one of important health indicator in assessment of health status of communities. For the moment in Indonesia the double nutrition problem (double burden), where the problem of over nutrition were blocked, but problems of under nutrition can’t to elimination. This study aimed to know prevalence nutritional status for elementary school pursuant to regional characteristic, sex, symptom of diseases, class level and knowledge of nutrition in Lubuklinggau municipality. The research design used cross sectional with multistage randomsampling method amount 6893 children. Nutritional status assessment used body mass index (BMI) percentile according to age groups and sex with reference of CDC 2000. The anthropometry data analysis used Epi Info version 3.3. Statistical analysis using chi square test with confidence interval 95 % and significant level 5 %. The result of research indicate that nutritional status with under weight category 36.1 %, over weight 2.9 % and obesity 2.5 %. Significant relation among nutritional status with regional characteristic (p 0.001), class level (p 0.001), sex (p 0.001), symptom of disease (p 0.003) and knowledge of nutrition (p 0.002)